2004
DOI: 10.1016/j.jacc.2004.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patency of saphenous vein and left internal mammary artery grafts after coronary artery bypass surgery

Abstract: The 10-year patency of IMA grafts is better than SVGs. The 10-year patency for SVGs is better and the 10-year patency for IMA grafts is worse than expected. The 10-year patency of SVGs to the LAD is better than that to the right or circumflex. The best long-term predictors of SVG graft patency are grafting into the LAD and grafting into a vessel that is >2.0 mm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
381
1
27

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 839 publications
(436 citation statements)
references
References 20 publications
12
381
1
27
Order By: Relevance
“…Coronary artery bypass grafting (CABG) 2 remains one of the most widely used surgical means of treating coronary heart disease after heart attack (1,2). Venous graft occlusion is the major cause of recurrent ischemia in patients after CABG.…”
mentioning
confidence: 99%
“…Coronary artery bypass grafting (CABG) 2 remains one of the most widely used surgical means of treating coronary heart disease after heart attack (1,2). Venous graft occlusion is the major cause of recurrent ischemia in patients after CABG.…”
mentioning
confidence: 99%
“…Nevertheless, the adverse effects of diabetes mellitus on graft patency have not been seen in all studies. For example, in a 10-year follow-up of the VA Cooperative Study involving 1074 CABG patients, Goldman et al 282 did not find diabetes mellitus to be an independent predictor of vein graft failure. Most recently, in a long-term observational study evaluating risk factors for adverse outcomes after CABG, Sabik et al 164 reported that diabetes mellitus was a strong risk factor for coronary reintervention (either percutaneous coronary intervention or redo CABG) in the years after CABG.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…[1,2] The LIMA is a unique artery in that it is more resistant to atherosclerosis due to its resilient endothelium and nonfenestrated internal elastic lamina that is resistant to smooth muscle migration. [2] In addition, the lumen of the LIMA is very close in size to that of the LAD, allowing for less turbulent flow after anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…All of these reasons mean that the LIMA to LAD has a superior 10 year patency to any other coronary bypass graft. [1,2] In situations where there is stenosis in the LAD distally to the original anastomosis, it would be ideal to take advantage of the well-documented benefits of this graft. Unfortunately, in re-operative CABGs adhesions around the LIMA can make it difficult to free and mobilize adequate length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation